MOF-derived electrochemical catalyst Cu–N/C for the enhancement of amperometric oxygen detection. Issue 5 (14th January 2022) - Yin, Wenyan; Zhang, Milin; Liu, Jingyuan; Alali, Khaled Tawfik; Yu, Jing; Zhu, Jiahui; Liu, Peili; Li, Rumin; Wang, Jun
Abstract : The incorporation of the ionic liquid 1-ethyl-2, 3-dimethylimidazole bis((trifluoromethyl)sulfonyl)imide and Cu–N/C into composite electrolytes provided a useful strategy to construct a tiny sensing unit for the determination of O2 concentration. Abstract : Electrochemical sensors using ionic liquids as electrolytes for oxygen detection are now getting more and more attention. Recently, an ionic liquid combined with an electrochemically active catalyst system has become popular for boosting the sensing performance of oxygen sensors. In this work, the imidazolyl-based ionic liquid 1-butyl-2, 3-dimethylimidazole bis((trifluoromethyl)sulfonyl)imide [Bmmim][TFSI] is first prepared by a facile two-step method. Subsequently, a transition metal and N-codoped porous carbon oxygen reduction electrochemical catalyst Cu–N/C is synthesized by calcining the Cu-doped ZIF-8 precursor and then blending it in different ratios with the ionic liquid [Bmmim][TFSI] as composite electrolytes for oxygen detection. The composite electrolyte Cu–N/C/[Bmmim][TFSI] exhibits increased responses in cyclic voltammetry (CV) and chronoamperometry (CA) relative to that of the pure ionic liquid. Furthermore, the CV and CA data show that 6% Cu–N/C/[Bmmim][TFSI] has the optimum oxygen sensing response with an enhanced reduction peak current, a sensitivity of 0.1678 μA/[% O2 ] and a good linear fitting coefficient of 0.9991. In conclusion, the results confirm the success of using Cu–N/C as an electrochemical catalyst composed of the Cu–N/C/[Bmmim][TFSI] electrolyte for improving the responsivity, stability and sensitivity towards a wide range of oxygen concentrations.